Protecting the Unprotected: A Legal Analysis of Guardianship for Underage Orphans - Aisyah Fadilah; Muhammad Rinaldy Bima; Jasmaniar Jasmaniar (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to analyze the guardianship of orphans who are still minors from the perspective of positive law in Indonesia. Orphans who have lost both parents need legal protection, especially in terms of guardianship arrangements that function to ensure the welfare and rights of the child. In this case, guardianship is an important aspect to provide a sense of security for children who need legal guidance, especially in determining who is responsible for fulfilling the child's living and educational needs. This study uses a normative research method, with an approach to relevant laws and regulations, as well as a literature study involving primary and secondary legal materials such as laws, literature, and related journals. This analysis also includes various regulations regarding child guardianship in Indonesian positive law, especially those regulating the status of orphans who have not reached adulthood. The results of the study show that in Indonesian positive law, guardianship of orphans is regulated in Law No. 23 of 2002 concerning Child Protection and Law No. 1 of 1974 concerning Marriage. The process of guardianship of orphans aims to provide custody to the person who is considered most worthy, either from the family or other parties who can provide the best protection for the child. However, in practice, there are still various obstacles, such as the lack of public understanding of the rights of orphans and weak supervision of the implementation of guardianship. Therefore, it is necessary to increase legal awareness in the community and strengthen the role of the state in supervising the guardianship of orphans.The recommendation from this study is to increase understanding of the guardianship rights of orphans and strengthen the implementation of legal protection for children, through education and closer cooperation between related institutions. Abstrak: Penelitian ini bertujuan untuk menganalisis perwalian anak yatim piatu yang masih di bawah umur dalam perspektif hukum positif di Indonesia. Anak yatim piatu yang kehilangan kedua orang tuanya memerlukan perlindungan hukum, khususnya dalam hal pengaturan perwalian yang berfungsi untuk memastikan kesejahteraan dan hak-hak anak tersebut. Dalam hal ini, perwalian merupakan aspek penting untuk memberikan rasa aman bagi anak yang membutuhkan bimbingan hukum, terutama dalam menentukan siapa yang bertanggung jawab atas pemenuhan kebutuhan hidup dan pendidikan anak. Penelitian ini menggunakan metode penelitian normatif, dengan pendekatan terhadap peraturan perundang-undangan yang relevan, serta studi pustaka yang melibatkan bahan hukum primer dan sekunder seperti Undang-Undang, literatur, dan jurnal terkait. Analisis ini juga mencakup berbagai peraturan mengenai perwalian anak dalam hukum positif Indonesia, khususnya yang mengatur status anak yatim piatu yang belum mencapai umur dewasa. Hasil penelitian menunjukkan bahwa dalam hukum positif Indonesia, perwalian anak yatim piatu diatur dalam Undang-Undang No. 23 Tahun 2002 tentang Perlindungan Anak dan Undang-Undang No. 1 Tahun 1974 tentang Perkawinan. Proses perwalian anak yatim piatu bertujuan untuk memberikan hak asuh kepada orang yang dianggap paling layak, baik dari keluarga atau pihak lain yang dapat memberikan perlindungan terbaik bagi anak. Namun, dalam praktiknya, masih terdapat berbagai kendala, seperti kurangnya pemahaman masyarakat mengenai hak-hak anak yatim piatu serta lemahnya pengawasan terhadap implementasi perwalian. Oleh karena itu, dibutuhkan peningkatan kesadaran hukum di masyarakat dan penguatan peran negara dalam pengawasan terhadap perwalian anak yatim piatu. Rekomendasi dari penelitian ini adalah untuk meningkatkan pemahaman tentang hak perwalian anak yatim piatu dan memperkuat implementasi perlindungan hukum bagi anak, melalui pendidikan dan kerjasama yang lebih erat antar lembaga terkait.